Quando a pena é forte como a espada: a autoimagem de muçulmanos de Mogi das Cruzes/SP face às representações do Islã na imprensa - Constantino, Heloisa (2015)
According to the media, Muslims tend to violence behavior, are not open to dialogue and oppress their women. This view comes from the representations made in the middle aged Europe and does not reflect the behavior of Islam s faithful people living in our country, but it also represents the imaginary of Brazilian people and interferes directly in the relations among the members of this religious group and the rest of the population. Considering that the Federal Constitution states that every citizen is free for practice the chosen religion, this work intends to analyze the attitude of the media that acts like an instrument of labelling, to demonstrate social mechanisms that cause this behavior of the media and to verify the consequences in the people that lives in Mogi das Cruzes Muslim Community